Development and Validation of a Coping Strategies Scale for Use in Chinese Contexts - Zhao, Jian; Chapman, Elaine; Houghton, Stephen; Lawrence, David (Frontiers in Psychology, 2022)
Individuals’ coping strategies have a profound effect on how well they respond to negative life events. Despite this, most coping strategies instruments that are available currently have been developed exclusively in Western contexts. In the present study, a Coping Strategies Scale (CSS) for use with Chinese participants was developed and validated based on responses from 734 Chinese university students (334 male, 399 female, 1 other). Results supported a seven-factor structure for the CSS, which included the dimensions of Withdrawal, Positive Adaptation, Problem-solving, Disengagement, Prosocial Focus, Seeking Emotional Support, and Self-regulation. The results supported the validity of the seven-factor CSS in terms of its content, associated response processes, internal structure, and relationships with other variables. Based on these results, the CSS provides a psychometrically sound instrument for assessing the coping strategies used by Chinese adults in confronting potentially adverse psychological events.